Hydrogen Peroxide-Forming NADH Oxidase Belonging to the Peroxiredoxin Oxidoreductase Family: Existence and Physiological Role in Bacteria - Nishiyama, Yoshitaka (American Society for Microbiology, 2001)
Amphibacillus xylanus and Sporolactobacillus inulinus NADH oxidases belonging to the peroxiredoxin oxidoreductase family show extremely high peroxide reductase activity for hydrogen peroxide and alkyl hydroperoxides in the presence of the small disulfide redox protein, AhpC (peroxiredoxin). In order to investigate the distribution of this enzyme system in bacteria, 15 bacterial strains were selected from typical aerobic, facultatively anaerobic, and anaerobic bacteria. AhpC-linked alkyl hydroperoxide reductase activities were detected in most of the tested strains, and especially high activities were shown in six bacterial species that grow well under aerobic conditions, including aerobic bacteria (Alcaligenes faecalis and Bacillus licheniformis) and facultatively anaerobic bacteria (Amphibacillus xylanus, Sporolactobacillus inulinus, Escherichia coli, and Salmonella enterica serovar Typhimurium). In the absence of AhpC, the purified enzymes from A. xylanus and S. inulinus catalyze the NADH-linked reduction of oxygen to hydrogen peroxide. Similar activities were observed in the cell extracts from each of these six strains. The cell extract of B. licheniformis revealed the highest AhpC-linked alkyl hydroperoxide reductase activity in the four strains, with V(max) values for hydrogen peroxide and alkyl hydroperoxides being similar to those for the enzymes from A. xylanus and S. inulinus. Southern blot analysis of the three strains probed with the A. xylanus peroxiredoxin reductase gene revealed single strong bands, which are presumably derived from the individual peroxiredoxin reductase genes. Single bands were also revealed in other strains which show high AhpC-linked reductase activities, suggesting that the NADH oxidases belonging to the peroxiredoxin oxidoreductase family are widely distributed and possibly play an important role both in the peroxide-scavenging systems and in an effective regeneration system for NAD in aerobically growing bacteria.